The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/gps.5050
|View full text |Cite
|
Sign up to set email alerts
|

Are overweight people more susceptible to anxiety?

Abstract: Objectives This study aimed to investigate anxiety status and its relationship with body mass index (BMI) among empty nesters in China, so as to improve their quality of life and provide direction for further research. Methods A cross‐sectional survey was conducted among 4901 empty nesters in Shanxi, China. Anxiety, weight, height, depression, socio‐demographic variables, attention to daily nutritional health, social activities, and self‐care ability were evaluated in the study. T‐tests and chi‐square tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…Several studies supported the hypothesis, suggested that there is a positive relationship between body weight and health. 52,53 However, our finding that obese people are more likely to have poor HRQoL did not support this notion. So is another recent study revealed that obesity exhibited no positive correlation with HRQoL among Chinese older adults.…”
Section: Discussioncontrasting
confidence: 71%
“…Several studies supported the hypothesis, suggested that there is a positive relationship between body weight and health. 52,53 However, our finding that obese people are more likely to have poor HRQoL did not support this notion. So is another recent study revealed that obesity exhibited no positive correlation with HRQoL among Chinese older adults.…”
Section: Discussioncontrasting
confidence: 71%
“…In our study, no differences were found by age. Differences among the three groups were also insignificant for BMI, smoking habits, and demographic characteristics, which are parameters that could independently affect HRQoL and psychological functioning, thus confounding our results [27,28].…”
Section: Discussionmentioning
confidence: 67%
“…Depression, anxiety, loneliness and other mental illnesses are common among empty nesters, and these mental illnesses seriously affect their quality of life [ 15 ]. Zhang et al found that 64.2% of empty nesters have depression [ 16 ], and 44.5% of empty nesters reported anxiety [ 17 ]. Mental health problems loom large for the empty nesters.…”
Section: Introductionmentioning
confidence: 99%